The Effect of High Concentrations of Glufosinate Ammonium on the Yield Components of Transgenic Spring Wheat (Triticum aestivum L.) Constitutively Expressing the bar Gene - Zoltán Áy; Róbert Mihály; Mátyás Cserháti; Éva Kótai; János Pauk (The Scientific World Journal)
We present an experiment done on a bar+ wheat line treated with 14 different concentrations of glufosinate ammonium—an effective component of nonselective herbicides—during seed germination in a closed experimental system. Yield components as number of spikes per plant, number of grains per spike, thousand kernel weight, and yield per plant were thoroughly analysed and statistically evaluated after harvesting. We found that a concentration of glufosinate ammonium 5000 times the lethal dose was not enough to inhibit the germination of transgenic plants expressing the bar gene. Extremely high concentrations of glufosinate ammonium caused a bushy phenotype, significantly lower numbers of grains per spike, and thousand kernel weights. Concerning the productivity, we observed that concentrations of glufosinate ammonium 64 times the lethal dose did not lead to yield depression. Our results draw attention to the possibilities implied in the transgenic approaches.